Unveiling dynamics of language visibility and vitality in café menus near Labrang Monastery - He, Min; Chen, Shengnan (Frontiers in Psychology, 2024)
Introduction This study explores the dynamics of Linguistic Landscapes (LL) in the commercial tourist district near Labrang Monastery by analyzing the use of Tibetan, Mandarin, and English on café menus. Traditionally, LL research has focused on language visibility as an indicator of vitality, overlooking contextual complexities. We challenge this approach by considering geocultural contexts, instigators’ language proficiency, and intended audience. Method This study employed a triangulation approach, combining multiple methods of data collection and analysis. First, we conducted a preliminary observation of shop names in the region. Second, with the consent of shop owners, we comprehensively documented visual and textual artifacts both inside and outside the cafés, including signboards, menus, wall billboards, and displayed books. Third, we conducted extensive semi-structured interviews with shop owners and customers. These interviews, transcribed for analysis, provided insights into language usage preferences and decision-making processes. Results By advocating for a holistic LL research approach, integrating qualitative insights with quantitative data, this study contributes to a deeper understanding of LL dynamics. Our findings show that geocultural contexts, instigators’ language proficiency, and intended audience all play a role in shaping language representation and vitality. Discussion The absence of a language on signage does not necessarily signify diminished vitality but can reflect strategic decisions influenced by religious, individual and commercial factors. Beyond mere visibility, languages on café menus serve as symbolic markers of ethnic identity and reflect the functions they assume within the speech community, offering insights into language vitality across different usage contexts. This research enriches scholarly discourse on LL, particularly within the Chinese context, by emphasizing the multifaceted nature of language presence and its vitality.